Outcomes following early parenteral nutrition use in preterm neonates: protocol for an observational study. Issue 7 (9th July 2019) - Webbe, James; Longford, Nicholas; Uthaya, Sabita; Modi, Neena; Gale, Chris
Abstract : Introduction: Preterm babies are among the highest users of parenteral nutrition (PN) of any patient group, but there is wide variation in commencement, duration, and composition of PN and uncertainty around which groups will benefit from early introduction. Recent studies in critically unwell adults and children suggest that harms, specifically increased rates of nosocomial infection, outweigh the benefits of early administration of PN. In this study, we will describe early PN use in neonatal units in England, Wales and Scotland. We will also evaluate if this is associated with differences in important neonatal outcomes in neonates born between 30 +0 and 32 +6 weeks +days gestation. Methods and analysis: We will use routinely collected data from all neonatal units in England, Wales and Scotland, available in the National Neonatal Research Database (NNRD). We will describe clinical practice in relation to any use of PN during the first 7 postnatal days among neonates admitted to neonatal care between 1 January 2012 and 31 December 2017. We will compare outcomes in neonates born between 30 +0 and 32 +6 weeks +days gestation who did or did not receive PN in the first week after birth using a propensity score-matched approach. The primary outcome will be survival to discharge home. Secondary outcomes will include components of the neonatal core outcome set: outcomes identified as important by former patients, parents, clinicians and researchers. Ethics and dissemination: We have obtained UK National Research Ethics Committee approval for this study (Ref: 18/NI/0214). The results of this study will be presented at academic conferences; the UK charity Bliss will aid dissemination to former patients and parents. Trial registration number: NCT03767634